IMF Staff papers : Volume 30 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1983)
This paper examines the conditions under which the monetary authorities of a large industrial country can influence the exchange rate while keeping the growth rate of the money stock on a predetermined target. Monetary policy in the large industrial countries has in recent years focused primarily on the achievement of predetermined growth rates for monetary aggregates. This study treats such intervention as an example of a broader class of combination policies that, for convenience, may be called 'sterilized policies.' In order to determine whether sterilized policies may be expected to be effective, this study examines the role of several specific types of monetary policy instrument in the context of a portfolio-balance model of financial markets. Each of the major countries employs a unique combination of policy instruments, ranging from market-oriented systems largely free of regulation to systems that rely heavily on quantitative ceilings and regulated interest rates. It is shown that sterilized changes in at least three of these instruments, as well as exchange market intervention, will have predictable effects on the exchange rate. The potentially effective instruments are reserve requirements on nonresident deposits or on deposits that are included in the targeted monetary aggregate, and controls on interest rates that are payable on such deposits.